1990
DOI: 10.1108/eum0000000001531
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and Passive Exporters: A Study in the Brazilian Furniture Industry

Abstract: The firm and chief executive officer correlates of aggressive export behaviour were examined in a random sample of 45 Brazilian wood‐furniture manufacturers. Because of the importance of earning foreign exchange to make payments on international loans, the Brazilian government has made major efforts to stimulate firms to export. This study examines whether the characteristics of aggressive exporters under such stimulation are different from those found in other environments. The results indicate that governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 8 publications
6
26
0
4
Order By: Relevance
“…For example, a foreign buyer intending to source a specific product may have contacted the association's headquarters or any of its members, who may refer the foreign buyer to another member, who is able to deliver that product in the desired time frame. As a result, industry association membership increases the probability of becoming a passive exporter, which is one of the first stages identified by the early exporting literature (da Rocha, Christensen, and Eduardo 1989;Wiedersheim-Paul, Olson, and Welch 1978). Member firms may also actively participate in events, business meetings, and trade fairs organized by the association, with the intention of becoming an exporter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a foreign buyer intending to source a specific product may have contacted the association's headquarters or any of its members, who may refer the foreign buyer to another member, who is able to deliver that product in the desired time frame. As a result, industry association membership increases the probability of becoming a passive exporter, which is one of the first stages identified by the early exporting literature (da Rocha, Christensen, and Eduardo 1989;Wiedersheim-Paul, Olson, and Welch 1978). Member firms may also actively participate in events, business meetings, and trade fairs organized by the association, with the intention of becoming an exporter.…”
Section: Discussionmentioning
confidence: 99%
“…The former factors include marketing strategy, organizational structure, managerial experience, and/or resource availability (Barney, 1991;Christensen et al, 1987;Culpan, 1989;Da Rocha and Christensen, 1994;Da Rocha et al, 1990;Dichtl et al, 1990;Katsikeas et al, 2000). External variables such as industry competitiveness, business environment, or product characteristics are also linked to export performance (Bain, 1951;Cavusgil and Zou, 1994;Cavusgil et al, 1993;Leonidou et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Once engaged in exploiting the opportunity, or in the process of internationalization, entrepreneurs are responsible for many internationalization-related tasks such as: setting objectives, gathering foreign market information, collecting and organizing resources, and implementing internationalization strategies. The degree of export aggressiveness to some extent refl ects the desire, willingness, and determination of the decisionmaker to promote the export side of business in the organization and this can, in turn, be attributed to certain entrepreneurial characteristics (de Rocha, Christensen & da Cunha, 1990;Leonidou, Katsikeas, & Piercy, 1998). Barney (1991), among others, suggested that resources lead to a sustained competitive advantage when they possess certain characteristics: value, rarity, inimitability, and nonsubstitutability.…”
Section: Dans La Présente éTude Nous Utilisons La Modélisa-tion Par mentioning
confidence: 99%